Spontaneous pneumomediastinum in limited cutaneous systemic sclerosis and myositis overlap. (30th July 2018) - Dein, Eric J; Lee, Kristen; Timlin, Homa; Hummers, Laura
Abstract : A 58-year-old man with limited cutaneous systemic sclerosis and myositis overlap complicated by interstitial lung disease presented with several months of progressive dyspnoea and weakness. CT chest revealed extensive pneumomediastinum that was not present on imaging 6 months before this study and appeared to be spontaneous, with no preceding trauma, infection or invasive procedures.